African swine fever virus RNA polymerase subunits C315R and H359L inhibition host translation by activating the PKR-eIF2a pathway and suppression inflammatory responses - Yang, Saixia; Wang, Yiwang; Yang, Jifei; Tian, Zhancheng; Wu, Mengli; Sun, Hualin; Zhang, Xiaoqiang; Zhao, Yaru; Luo, Jianxun; Guan, Guiquan; Yin, Hong; Hao, Rongzeng; et al. (Frontiers in Microbiology, 2024)
ASFV C315R is homologous to the transcription factor TFIIB of large unclassified DNA viruses, and H359L is identical to the subunit 3 (RPB3) of eukaryotic RNA polymerase II. The C315R and H359L may play an important role in ASFV replication and transcription. Here, we evaluated the biological function of the C315R and H359L genes during virus replication in vitro and during infection in pigs. Results showed that C315R and H359L are highly conserved among ASFV genotype II strains; quantitative PCR (qPCR) and western blotting analyses revealed that C315R and H359L are early transcribed genes prior to viral DNA replication, but their protein expression is delayed. The immunofluorescence and western blotting analysis revealed that both proteins localized in the cell cytoplasm and nucleus at 24 h post infection, however, pH359L was mainly detected in the cell cytoplasm. Furthermore, overexpression of pH359L in MA104 cells significantly increased viral titer, RNA transcription levels, and viral protein expression levels, while overexpression of pC315R slightly enhanced ASFV replication. In contrast, siRNA targeting ASFV-H359L or C315R reduced replication efficiency in porcine macrophage culture compared to the parent ASFV-CN/SC/2019, demonstrating that C315R and H359L genes are necessary for ASFV replication. Finally, the functional role of C315R or H359L on PKR and eIF2α phosphorylation status and SG formation, as well as cytokine production were evaluated. These studies demonstrated that C315R and H359L are involved in virus replication processes in swine and play important roles in ASFV replication.